THE RESULTS OF EXPERT ASSESSMENT OF PSYCHOTHERAPEUTIC AID TO ADULT POPULATION OF NOVOSIBIRSK REGION - V. Yu. Chaplygina; I. A. Tsytsorina; Ya. V. Khmelnitskaya (Сибирский научный медицинский журнал, 2019)
Research objective – assessment of the state, organization, issues and development outlook of psychotherapeutic aid at the regional level. Material and methods. The expert card permitting to carry out expert assessment of psychotherapeutic aid at the regional level was developed. The standard method was used for expert assessment. The method of concordance with the Kendall coefficient (W) was used to determine the consistency of experts’ opinions. Experts were the health professionals, psychotherapists, psychiatrists. 156 experts took part in the assessment. Results: According to the opinion of 61.1 ± 4.8 % of the experts, psychotherapeutic aid is in high demand at the stage of primary health care, but at the same time 70.5 ± 4.5 % of the experts believe that it is less available at this stage (W = 0.4; p < 0.001). 68.5 ± 4.6 % of the experts feel that the amount of psychotherapeutic aid, administered to adult population in the territory of Novosibirsk region, is insufficient (W = 0.3; p < 0.001). According to 85.9 ± 3.4 % of the experts, the development of availability of such aid is necessary. Conclusion: Increase in awareness concerning psychotherapeutic aid among doctors and patients, as well as opening of psychotherapeutic offices as part of standard polyclinics, rise in the number of psychotherapeutists and introduction of psychotherapy into the compulsory health insurance system will facilitate the improvement of the management of psychotherapeutic aid at the regional level.